Hemibeltrania urbanodendrii sp. nov. and Pseudobeltrania angamosensis: new fungal records from the brazilian tropical seasonal semi-deciduous montane forest - Fernandes,Ronaldo de Castro (2007)
The new species Hemibeltrania urbanodendrii, associated to leaf-spots on Urbanodendron verrucosum (Lauracea) and Pseudobeltrania angamosensis, associated with leaf-spots on Virola gardneri (Myristicaceae), are recorded for the first time in Brazil. They represent additions to the mycobiota of the Tropical Seasonal Semi-Deciduous Montane Forest in Viçosa (Minas Gerais, Brazil), a highly threatened ecosystem.